2020
DOI: 10.1002/kjm2.12199
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and its dimers ε‐viniferin and δ‐viniferin in red wine protect vascular endothelial cells by a similar mechanism with different potency and efficacy

Abstract: Red wine compounds have been reported to reduce the rate of atherosclerosis by inducing nitric oxide (NO) production and antioxidant enzyme expression in vascular endothelial cells (VECs). The present study compared the effects of the three red wine compounds resveratrol and its dimers, ε-viniferin and δ-viniferin, on VECs function for the first time. Both 5 μM ε-viniferin and δ-viniferin, but not 5 μM resveratrol, significantly stimulated wound repair of VECs. Increased levels of wound repair induced by 10 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…ICAM-1, VCAM-1, E-selectin, and MCP-1 are biomarkers of endothelial dysfunction in atherosclerosis [ 23 , 41 , 42 ]. We incubated VECs with 1, 5, 15, and 45 µM heliangin for 24 h, and then assayed cell viability using trypan blue staining.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ICAM-1, VCAM-1, E-selectin, and MCP-1 are biomarkers of endothelial dysfunction in atherosclerosis [ 23 , 41 , 42 ]. We incubated VECs with 1, 5, 15, and 45 µM heliangin for 24 h, and then assayed cell viability using trypan blue staining.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were used between passages 8 and 10 for bioassay. The cells were incubated in DMEM containing 1% FBS for 17 h before starting the experiments [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, if molecules (>4 kDa) and microorganisms cross mucous membrane and epithelial barrier, it will retain the LP, unless GVB is destroyed resulting in a change in permeability ( 83 ). Studies have shown that resveratrol reduces vascular oxidative stress, relieves vascular inflammation, and improves vascular function ( 84 , 85 ). Besides, resveratrol decreases small intestinal pro-inflammatory cytokines and gut vascular permeability, which could attenuate the blood levels of pro-inflammatory cytokines from small intestine and alleviate cytokines-mediated BBB disruption and neuroinflammation ( 76 ).…”
Section: Resveratrol and Intestinal Barriermentioning
confidence: 99%